“Local Food” Consumption: Does Locality Matter? - Agustina Multi Purnomo; Gumilar Rusliwa Somantri; Ricardi S. Adnan (JAS (Journal of ASEAN Studies), 2023)
The research examined the possibility of food being socialized as local food to replace local food’s role in food tourism. Food was one of the major attractions during a vacancy in ASEAN. The study of food in tourism rarely considered local food diversity in urban areas. The research addressed the other type of local food that is typical city food. In this case, there is no connection between the food and culture, traditions, history, or place, but the food is socialized as being indigenous. The local food consumption model was used to test whether the factors that affect tourists' local food consumption apply equally to foods socialized as local food. The research compared domestic tourist local food consumption factors in two food categories. 640 domestic tourists in a developed culinary tourism city in the Jakarta Metropolitan Area participated in this online survey. The comparative test of tourist characteristics found gender, the purpose of visit, age, and status of visit tourist characteristics associated with the food choice. The physical environment, exiting experience, and authentic experience were the motivational factors that differed between two food categories. It is possible that socialized foods will replace local food. The food locality did not always a matter. The results provide an overview of the position of local food in urban tourism. This has been considered the main attraction of food tourism in ASEAN countries.